EFEKTIVITAS SENAM LANSIA TERHADAP PENURUNAN TEKANAN DARAH : Literature Review - Junaedi Yunding; Irna Megawaty; Anna Aulia (Borneo Nursing Journal (BNJ), 2021)
Blood pressure is a description of a person's hemodynamic situation at that time. Hemodynamics is a condition where pressure and blood flow can maintain the exchange or perfusion of substances in the tissues. Especially for the elderly, one way to maintain the hemodynamic condition is to exercise. The sport used is elderly gymnastics. Elderly exercise can prevent or slow down functional loss of organs and can also eliminate various risks of diseases such as hypertension, diabetes mellitus, and coronary artery disease. The purpose of the literature is to find out more closely related to the effectiveness of elderly exercise on reducing blood pressure. Method, In this literature review, the collection of relevant articles was obtained in the Pubmed database and Google Scholar with a time span of May 1, 2014 to May 31, 2020 (5 years). The results and conclusions, based on the results of the review that has been done, it can be concluded that there is an influence of elderly exercise to reduce blood pressure in the elderly. Decreased blood pressure occurs because the blood vessels experience widening and relaxation. Over time, exercise can relax blood vessels so that blood pressure decreases.